THE EFFECTIVENESS OF "PEER GROUP DISCUSSION" IN IMPROVING HEALTH CADRE'S KNOWLEDGE ABOUT DANGER SIGNS IN THE MATERNAL PERIODS - Ermiati E; Anita Setyawati; Etika Emaliyawati (Journal of Maternity Care and Reproductive Health, 2018)
Limited health literacy is one of the causes of late detection related to danger signs in pregnancy, postpartum and newborns. Health cadres are one of the main resources for early detection and dissemination of health information in the community. The purpose of this study was to determine the effectiveness of the peer group discussion method in increasing the knowledge of health cadres about danger signs in pregnancy, postpartum and new-borns (maternal periods). This research was Quasi-experimental study with a pre-test and post-test design. The stages of intervention in this study included training on danger signs with the lecture method followed by small group discussions (5-6 people) for 30 minutes, and practicing early warning signs detection. Questionnaires were given before and after training. The population in the study were all health cadres at Penanjung Health Center, while the sample was 32 health cadres from the health post (POSYANDU) Sari Asih. The Wilcoxon test was used to determine whether there was a difference in knowledge before and after training. The results showed the midpoint of the pregnancy danger signs before intervention 66.7 and after the intervention was 100. Middle value of postpartum danger signs knowledge before intervention 70 and after intervention 100. Midpoint knowledge of danger signs in newborns before intervention 75 and after intervention 100.  The results of the bivariate analysis of the Wilcoxon Test before and after the intervention showed a p-value of 0,000 which means that there were significant differences before and after the intervention related to the danger signs in the maternal periods. Training on health cadres with this method increases cadres’ knowledge about danger signs in pregnancy, postpartum and newborns.Keywords: Danger sign, health care, newborns, postpartum, pregnancy, training